The Ideology of Neoconservatism: Theoretical and Political-Categorical Analysis (Texas Journal of Multidisciplinary Studies, 2022)
This article analyzes the ideology of U.S. neoconservatism, one of the modern political ideologies, focusing on the theoretical and political-categorical issues of ideology.